Historical perspective on the department of energy mortality studies: focus on the collection and storage of individual worker data. (3rd April 2022) - Ellis, Elizabeth D.; Girardi, David; Golden, Ashley P.; Wallace, Phil W.; Phillips, Joyce; Cragle, Donna L.
Abstract: Purpose: To present how the Department of Energy's (DOE) Comprehensive Epidemiologic Data Resource (CEDR) is integrated into the Million Person Study of Low Dose Health Effects (MPS). The history of DOE's worker health surveillance and its epidemiology program are described. Methods and materials: A standard protocol is used to extract data from CEDR for use in the MPS. The data files are pulled from CEDR to form the basis for the cohort analyzed in the MPS. The previous study data are reviewed to formulate the protocol for the MPS study cohort. The activities needed to update the data to construct the new analytic files are carried out in parallel. The primary efforts relate to updating the vital status, retrieving cause of death information and calculating annual radiation doses for the specific organs of interest. Working data files containing the updated data are produced for construction of analytic data files used in the biostatistical analysis. At study completion the working and analytic data files are placed into CEDR for use by other researchers. Results: The use of CEDR to study the scientific and maintenance workers at the Los Alamos National Laboratory which is currently underway is used to demonstrate the process. Conclusions: There is a pressing need to answer the question of the health risk of exposure to chronic low-level exposure to ionizing radiation. Using CEDR as the starting point to identify new cohorts to include in the MPS is a cost-effective and a time efficient way to expedite answering this question.